Curvas esféricas com curvatura proporcional a função altura - Furtado, Miriam Cristina Ferreira (2024)
In the work, we analyze the study by [17] on the characterization of soliton solutions of the Curve Shortening Flow (CSF) on revolution surfaces in the space R³, demonstrating that such solutions asymptote the parallels that are geodesics. Furthermore, we will address the work carried out by [8] that characterizes soliton solutions on the unitary sphere S². We will apply a similar methodology to describe curves with curvature depends on the height function